GOOD GOVERNANCEIN VILLAGE FINANCIAL MANAGEMENT (STUDY OF ANGKAES VILLAGE, WELIMAN DISTRICT, MALAKA REGENCY, EAST NUSA TENGGARA) - Maria Akripina Mau; Marisa S. B. Seran; Surya Yudha Regif; Andre Pattipeilohy; Yohannes Imanuel Naif; Dimas Agustian; Fransin Kontu; Eunike S. Pelleng; Faisal Fadilla Noorikhsan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine the application of Good Governance principles in village financial management, especially in Angkaes Village, Weliman District, Malaka Regency. The problem underlying this study is the obstacles still found in village financial management, such as limited transparency, community participation, and accountability of village officials in every stage of management. This study uses a qualitative descriptive method with data collection techniques through interviews, observation, and documentation. Research informants were determined purposively involving village officials, the Village Consultative Body (BPD), and the local community. The results of the study indicate that the application of Good Governance principles in village financial management in Angkaes Village is not yet fully optimal. Transparency has begun to be implemented through the APBDes information board and village deliberations, but has not been implemented consistently. Community participation in planning and supervision is still low due to a lack of socialization. The accountability of village officials also still faces obstacles related to accountability reports that are not fully in accordance with the provisions. Thus, this study concludes that although the principles of Good Governance have become a guideline in village financial management, the practice still needs to be improved through strengthening the capacity of village officials, increasing community involvement, and enforcing a more transparent and accountable monitoring system.